2017
DOI: 10.1007/s10565-017-9411-z
|View full text |Cite
|
Sign up to set email alerts
|

Costunolide induces micronuclei formation, chromosomal aberrations, cytostasis, and mitochondrial-mediated apoptosis in Chinese hamster ovary cells

Abstract: Costunolide (CE) is a sesquiterpene lactone well-known for its antihepatotoxic, antiulcer, and anticancer activities. The present study focused on the evaluation of the cytogenetic toxicity and cellular death-inducing potential of CE in CHO cells, an epithelial cell line derived from normal ovary cells of Chinese hamster. The cytotoxic effect denoting MTT assay has shown an IC value of 7.56 μM CE, where 50% proliferation inhibition occurs. The oxidative stress caused by CE was confirmed based on GSH depletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…It should be further explored whether the variation between nuclear and mitochondrial DNA and degrees of MtDNA mutations may influence the specificity and sensitivity of MtDNA or the processes of MtDNA replication, transcription, and termination. In addition to the measurement of mitochondrial function after drug delivery, drugs can induce micronuclei formation, chromosomal aberrations, cytostasis, and mitochondrial-mediated apoptosis as part of the cytogenetic toxicity in CBT (Singireesu et al 2017).…”
Section: Initiating and Terminating The Signalingmentioning
confidence: 99%
“…It should be further explored whether the variation between nuclear and mitochondrial DNA and degrees of MtDNA mutations may influence the specificity and sensitivity of MtDNA or the processes of MtDNA replication, transcription, and termination. In addition to the measurement of mitochondrial function after drug delivery, drugs can induce micronuclei formation, chromosomal aberrations, cytostasis, and mitochondrial-mediated apoptosis as part of the cytogenetic toxicity in CBT (Singireesu et al 2017).…”
Section: Initiating and Terminating The Signalingmentioning
confidence: 99%
“…Recent studies have shown that the ethanol extract of Aucklandia lappa Decne has anti-cancer effect on prostate cancer, oral cancer, breast cancer, and cervical cancer [10][11][12]. In addition to its anti-tumor chemo-preventive effect, Costunolide also has anti-cancer activity against various cancer cells such as lung cancer, breast cancer, and liver cancer, and can inhibit the invasion and metastasis of cancer cells [13][14][15][16][17][18][19]. Although Berberine and Costunolide have decent anti-cancer activity, it is not clear whether Berberine and Costunolide are key functional components of DHW, and the benefits of this combination for liver cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Costunolide is in part effective by decreasing vascular endothelial growth factor (VEGF) [3], interleukin (IL)-1β, IL-6, IL-17 [3], tumor necrosis factor (TNF)-α [3] and transforming growth factor (TGF-β) [3]. Costunolide induces oxidative stress [2,11,[15][16][17][18] and fosters apoptosis of tumor cells [1,2,11,[16][17][18][19][20][21][22][23][24]. On the other hand costunolide protects against oxidative stress [25].…”
Section: Introductionmentioning
confidence: 99%
“…Signaling involved in the effects of Costulonide includes stimulation of mitogen-activated kinases [20,26] as well as inhibition of the transcription factor NFκB [10,13,15] and the Wnt/β-Catenin Pathway [9]. The stimulation of apoptosis further involves mitochondria [19,27].…”
Section: Introductionmentioning
confidence: 99%